PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING - Putro, Vinki Permata Sari Utomo; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of corporate social responsibility to the firm value and to test the profitability which moderate the influence of corporate social responsibility to the firm value of mining companies which are listed in Indonesia Stock Exchange. The samples are 13 mining companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2015 periods with the number of observations is 52 and these companies have been selected by using purposive sampling method. The results of this research indicates that corporate social responsibility does not give any influence to the firm value, it means that the size of CSR which has been run by the company does not give any influence to the enhancement of firm value. It is caused by the investors in Indonesia tend to buy and to sell stocks without regarding to the long term sustainability of the company. Profitability moderates the influence of corporate social responsibility to the firm value due to the ROE shows the ability of the company in generating profits and the high rate of return of the own capital.Keywords: corporate social responsibility, firm value, profitability.